(untitled) (International Journal of Economics Management and Social Science, 2026)
Education is often viewed as an engine of social mobility and democratization of opportunity, yet critical theories in sociology of education reveal that educational institutions actually function to reproduce and legitimize existing social stratification. This article analyzes the mechanisms of cultural reproduction operating within educational systems, focusing on the theoretical contributions of Pierre Bourdieu, Basil Bernstein, and Paul Willis to understanding how schools perpetuate social inequality. Through a qualitative approach employing systematic literature review of classical works and recent empirical research (2018-2025), this study explores three critical dimensions: (1) the role of cultural capital, habitus, and symbolic violence in reproducing class structures; (2) mechanisms of pedagogic discourse and linguistic codes that perpetuate middle-class dominance; and (3) working-class resistance and formation of counter-school identities as responses to educational marginalization. Findings indicate that hidden curriculum, tracking practices, evaluation systems, and teacher expectations systematically advantage students from middle-upper classes who possess cultural capital aligned with school dispositions. Working-class students face dissonance between family habitus and scholastic habitus, encounter difficulties accessing the elaborated code privileged by schools, and often develop anti-school cultures as resistance strategies that paradoxically reinforce their class destinations. This article identifies five reproduction mechanisms: differential selection based on cultural capital, legitimization of success through meritocratic ideology, transmission of tacit knowledge through hidden curriculum, institutionalization of symbolic domination through standardization, and counterproductive resistance. The theoretical implications enrich critical sociology of education by integrating structuralist, culturalist, and ethnographic perspectives, while practical implications point to the urgency of epistemic democratization and critical pedagogy recognizing multiple forms of knowledge to interrupt cycles of social reproduction. Keywords: Sociology of Education, Cultural Reproduction, Social Stratification, Cultural Capital, Habitus, Hidden Curriculum, Pierre Bourdieu, Basil Bernstein, Paul Willis